Occupational Health Exposure and Perceived Effects of Portland Cement Dust Pollution on Cement Factory Workers - Ndinwa, Gabriel C. C; Chukumah, Charity O; Akpafun, Solomon A (Journal of Atmosphere, 2020)
The perceived occupational and environmental health challenges arising from the exposure of cement dust pollution on Bua cement factory workers were investigated in this study to establish if there is any significance of cement dust exposure on workers’ health. The study was designed as a cross-sectional type of research that adopted a purposive group based strategy for sampling. 110 cement factory workers with a minimum of two years’ work experience were selected for the study. 90 respondents were randomly selected from a community situated at about 21km away from the factory and used as control. Structured questionnaire was used for data collection and SPSS statistical package was used to analyze the data. Inferential statistics was used to test the hypotheses at p <0.05, ascertain correlation of the variables and authenticate the analysed results. The result revealed that 15 types of ailment were reported among the sampled respondents with factory workers recording higher percentage occurrence of ailments than respondents from the control. Factory workers were more susceptible to the itemized ailments recorded when compared to respondents from control. Significant difference in the prevalence of perceived health ailments between factory workers and control was established. Workers from storage and transportation section were revealed to have higher percentage (77.3%) compliance level on the use of safety gadgets during work hours than workers from other sections. Also, a significant relationship between the perceived health risks associated with cement dust exposure and the health of factory workers was established. The researchers made reasonable recommendations to forestall further health complications that might arise from working on a cement production factory.